Relationship Depth and Associative Stigma of Disability - Nieweglowski, Katherine; Sheehan, Lindsay (Disability Studies Quarterly, 2017)
Family, friends and acquaintances of people with disabilities may be viewed or treated differently by the public due to their association with a stigmatized person. Previous research finds that the public are more willing to engage in relationships with people with physical disability than with mental illness. In addition, attitudes towards associating with people with disabilities has been found to vary by depth of the chosen relationship. The current study sought to examine the connections between relationship depth (friend/romantic partner/acquaintance), disability type (physical/psychiatric) and associative stigma. Adult participants (N=345) were randomly presented with vignettes varying in relationship depth and disability type via an online survey platform. Analyses found no differences in associative stigma between physical and psychiatric disabilities. Participants viewed the vignette actor Rachel as socially warmer when she was a friend or romantic partner of a person with a disability than when she was an acquaintance. Participants rated Rachel as different from themselves when she was romantically involved with the person with disability and were more willing to engage socially with Rachel when she befriended the person with disability rather than when she was a mere acquaintance.